Unveiling and Imaging Degenerate States in Plasmonic Nanoparticles with Nanometer Resolution - Myroshnychenko, Viktor; Nishio, Natsuki; García de Abajo, F. Javier; Förstner, Jens; Yamamoto, Naoki (ACS Nano)
Metal nanoparticles host localized plasmon excitations that allow the manipulation of optical fields at the nanoscale. Despite the availability of several techniques for imaging plasmons, direct access into the symmetries of these excitations remains elusive, thus hindering progress in the development of applications. Here, we present a combination of angle-, polarization-, and space-resolved cathodoluminescence spectroscopy methods to selectively access the symmetry and degeneracy of plasmonic states in lithographically fabricated gold nanoprisms. We experimentally reveal and spatially map degenerate states of multipole plasmon modes with nanometer spatial resolution and further provide recipes for resolving optically dark and out-of-plane modes. Full-wave simulations in conjunction with a simple tight-binding model explain the complex plasmon structure in these particles and reveal intriguing mode-symmetry phenomena. Our approach introduces systematics for a comprehensive symmetry characterization of plasmonic states in high-symmetry nanostructures.
Keywords: tet_topic_plasmonics

Direction-tunable enhanced emission from a subwavelength metallic double-nanoslit structure - Song, Xiaohong; Wang, Nini; Yan, Ming; Lin, Cheng; Förstner, Jens; Yang, Weifeng (Optics Express)
Controlling light emission out of subwavelength nanoslit/aperture structures is of great important for highly integrated photonic circuits. Here we propose a new method to achieve direction-tunable emission based on a compact metallic microcavity with double nanoslit. Our method combines the principles of Young’s interference and surface plasmon polaritons interference. We show that the direction of the far-field beam can be controlled over a wide range of angles by manipulating the frequency and relative phase of light arriving at the two slits, which holds promise for applications in the ultracompact optoelectronic devices.
Keywords: tet_topic_plasmonics

Discrete plasmonic solitons in graphene-coated nanowire arrays - Kou, Yao; Förstner, Jens (Optics Express)
e study the discrete soliton formation in one- and two- dimensional arrays of nanowires coated with graphene monolayers. Highly confined solitons, including the fundamental and the higher-order modes, are found to be supported by the proposed structure with a low level of power flow. Numerical analysis reveals that, by tuning the input intensity and Fermi energy, the beam diffraction, soliton dimension and propagation loss can be fully controlled in a broad range, indicating potential values of the graphene-based solitons in nonlinear/active nanophotonic systems.
Keywords: tet_topic_plasmonics; tet_topic_polariton

Unveiling Nanometer Scale Extinction and Scattering Phenomena through Combined Electron Energy Loss Spectroscopy and Cathodoluminescence Measurements - Losquin, Arthur; Zagonel, Luiz F.; Myroshnychenko, Viktor; Rodríguez-González, Benito; Tencé, Marcel; Scarabelli, Leonardo; Förstner, Jens; Liz-Marzán, Luis M.; García de Abajo, F. Javier; Stéphan, Odile; Kociak, Mathieu (Nano Letters)
Plasmon modes of the exact same individual gold nanoprisms are investigated through combined nanometer-resolved electron energy-loss spectroscopy (EELS) and cathodoluminescence (CL) measurements. We show that CL only probes the radiative modes, in contrast to EELS, which additionally reveals dark modes. The combination of both techniques on the same particles thus provides complementary information and also demonstrates that although the radiative modes give rise to very similar spatial distributions when probed by EELS or CL, their resonant energies appear to be different. We trace this phenomenon back to plasmon dissipation, which affects in different ways the plasmon signatures probed by these techniques. Our experiments are in agreement with electromagnetic numerical simulations and can be further interpreted within the framework of a quasistatic analytical model. We therefore demonstrate that CL and EELS are closely related to optical scattering and extinction, respectively, with the addition of nanometer spatial resolution.
Keywords: tet_topic_plasmonics

Coupling Mediated Coherent Control of Localized Surface Plasmon Polaritons - Zeuner, Franziska; Muldarisnur, Mulda; Hildebrandt, Andre; Förstner, Jens; Zentgraf, Thomas (Nano Letters)
Keywords: tet_topic_plasmonics

Optimization of the intensity enhancement in plasmonic nanoantennas - Hildebrandt, Andre; Reichelt, Matthias; Meier, Torsten; Förstner, Jens
We design the geometrical shape of plasmonic nanostructures to achieve field patterns with desired properties. For this, we combine Maxwell simulations and automatic optimization techniques. By allowing variations of the geometrical shape, which can be based on either boxes or arbitrary polygons, we maximize the desired objective.
Keywords: tet_topic_optical antenna; tet_topic_plasmonics